Latent Membrane Protein 1 of Epstein-Barr Virus Inhibits as Well as Stimulates Gene Expression - Sandberg, Mark L. (American Society for Microbiology, 2000)
The latent membrane protein 1 (LMP-1) of Epstein-Barr virus (EBV) functionally resembles a constitutively active, CD40-like receptor and contributes to the maintenance of proliferation of EBV-infected primary human B lymphocytes. LMP-1 is targeted to the plasma membrane, where it binds TRAF, TRADD, and JAK molecules to activate NF-κB-, AP-1-, and STAT-dependent pathways as does CD40. Yet LMP-1 appears to lack a ligand to regulate its signaling. We have found that LMP-1, when expressed at physiologic levels, inhibits gene expression detectably. Higher levels of LMP-1 expression eventually inhibit both the steady-state level of RNA produced from a BamHI C promoter reporter and general cellular protein synthesis. These findings indicate that LMP-1 can limit its signaling and that this control is manifest at two levels. The domain of LMP-1 that binds TRAF, TRADD, and JAK/STAT molecules is not required for this regulation. A derivative of LMP-1 that contains only its amino-terminal and membrane-spanning domains is sufficient to inhibit reporter activity when the reporter genes are expressed from the BamHI C and LMP-1 promoters. This same derivative of LMP-1 in parallel assays is sufficient to inhibit wild-type LMP-1's stimulation of NF-κB-dependent gene expression. We suggest that LMP-1 encodes stimulatory and inhibitory activities; the latter could limit signaling in the apparent absence of ligand-dependent down-regulation.